2015
DOI: 10.1016/j.neuropsychologia.2015.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Severely deficient autobiographical memory (SDAM) in healthy adults: A new mnemonic syndrome

Abstract: Recollection of previously experienced events is a key element of human memory that entails recovery of spatial, perceptual, and mental state details. While deficits in this capacity in association with brain disease have serious functional consequences, little is known about individual differences in autobiographical memory (AM) in healthy individuals. Recently, healthy adults with highly superior autobiographical capacities have been identified (e.g., LePort, A.K., Mattfeld, A.T., Dickinson-Anson, H., Fallon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
91
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(101 citation statements)
references
References 79 publications
10
91
0
Order By: Relevance
“…However, Galton's finding that some scientists had extremely limited or zero imagery raises questions about the influence this other pole has had on the evolution of science and mathematics which I think should be revisited in the light of the new evidence from Zeman et al (2015) about aphantasia. I have recounted my own experience of becoming aware of my aphantasia and a concomitant memory issue, SDAM, and the work of Palombo et al (2015) in providing objective evidence of the latter. My participation as a research subject for their paper provided me with gratifying empirical evidence that what I thought was happening was indeed real, but, equally, confirmed that it is limited in its scope, and hasn't stopped me living an essentially normal life.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Galton's finding that some scientists had extremely limited or zero imagery raises questions about the influence this other pole has had on the evolution of science and mathematics which I think should be revisited in the light of the new evidence from Zeman et al (2015) about aphantasia. I have recounted my own experience of becoming aware of my aphantasia and a concomitant memory issue, SDAM, and the work of Palombo et al (2015) in providing objective evidence of the latter. My participation as a research subject for their paper provided me with gratifying empirical evidence that what I thought was happening was indeed real, but, equally, confirmed that it is limited in its scope, and hasn't stopped me living an essentially normal life.…”
Section: Discussionmentioning
confidence: 99%
“…These phrases are so familiar that most people take for granted the three human capacities they embody: visual imagination; "episodic" memory that directly reexperiences one's own past sights, sensations and emotions; and its temporal opposite, first person "mental time travel" into an anticipated future. Most people, but not all, as was apparently first noticed by Galton (1880) and is now becoming clearer through the work of Palombo et al (2015) on SDAM and Zeman et al (2015) on aphantasia. I am somebody who lacks all these three capacities, and the rest of this paper is about my quest, both as a physicist and a person, to understand why, and to come to terms with these differences.…”
Section: T Learn Much Algebra I Just Learnt How Better To Think In Pmentioning
confidence: 92%
See 1 more Smart Citation
“…The absence of these features, together with the distinctive pattern of CS' amnesia (see 4.5), and the resolution of her amnestic episodes and ALF on withdrawal of baclofen, argue strongly for a pharmacological rather than a psychological explanation for her memory symptoms. Such cases suggest that selective Aba can arise from a range of different pathologies, including i) diffuse pathology (Evans JJ, Breen EK, Antoun N, & Hodges JR, 1996;Evans, Graham, Pratt, & Hodges, 2003), ii) right temporofrontal pathology (Levine B et al, 1998;Levine, Svoboda, Turner, Mandic, & Mackey, 2009), iii) visual cortical pathology (Rubin & Greenberg, 1998), iv) temporal lobe epilepsy (Tramoni et al, 2011;Jansari, Davis, McGibbon, Firminger, & Kapur, 2010;Hornberger et al, 2010;Butler et al, 2007) as well as v) functional or dissociative amnesia (Staniloiu & Markowitsch H, 2014;Markowitsch & Staniloiu, 2013) and the recently described syndrome of 'severely deficient autobiographical amnesia in healthy adults' (Palombo, Alain, Soderlund, Khuu, & Levine, 2015). This wide range of potential causes might be predicted from the existence of a complex network subserving autobiographical memory (Svoboda, McKinnon, & Levine, 2006).…”
Section: I) In the Case Report (31) We Have Added Relevant Informatimentioning
confidence: 99%
“…Indeed, a meta‐analysis of functional magnetic resonance imaging (fMRI) studies of episodic retrieval revealed only limited anatomical overlap in the neural correlates associated with the retrieval of laboratory‐encoded and autobiographical memories . Moreover, performance on standard laboratory‐based memory tasks can be largely unrelated to one's autobiographical retrieval abilities, as demonstrated by individuals with either “highly superior autobiographical memory” or “severely deficient autobiographical memory.” Dissociations like these have led some to propose that retrieving autobiographical event knowledge is fundamentally different from other forms of episodic retrieval …”
Section: Introductionmentioning
confidence: 99%